AN ANALISIS OF PAKEM APPROACH - Chamisah, Chamisah (English Department of Faculty of Tarbiyah and Teachers Training, 2012)
This article aims to explain the consep of PAKEM approach in accordance with the principle of particular learning model,namely,active learning, creative learning, effective lerning,and joyful learning. The elaboration of this issue will Â relate to the condition of teaching learning prosess. Due to that point, the characteristics of implementing PAKEM are introduced. It uses various sources of learning, and applies various activities based on these.Â Â In addition the results of studentsâ creativities are displayed. Â Furthermore, the teachers apply various methods of teaching and at the end of activity, the teacher together with students do reflection and usually when doing evaluation, teachers apply classroom based assessment that focuses on its process. In line with this, this article also explains some consideration when applying this approach such as understanding studentsâ behaviors as an individual and in a group. Finally it explains about the process of teaching learning process.